2023
DOI: 10.1126/sciadv.adf0567
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory CD4/CD8 double-positive human T cells arise from reactive CD8 T cells and are sufficient to mediate GVHD pathology

Abstract: An important paradigm in allogeneic hematopoietic cell transplantations (allo-HCTs) is the prevention of graft-versus-host disease (GVHD) while preserving the graft-versus-leukemia (GVL) activity of donor T cells. From an observational clinical study of adult allo-HCT recipients, we identified a CD4 + /CD8 + double-positive T cell (DPT) population, not present in starting grafts, whose presence was predictive of ≥ grade 2 GVHD. Using an established xenogeneic tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In addition, the expansion of DP T cells in RA is associated with joint damage and frequent escalation of therapy [70]. Another example of DP T cell presence in inflammation is the development of graft versus host disease (GVHD), which has been recently associated with the appearance of a DP T cell population that was originally not present in the graft [72].…”
mentioning
confidence: 99%
“…In addition, the expansion of DP T cells in RA is associated with joint damage and frequent escalation of therapy [70]. Another example of DP T cell presence in inflammation is the development of graft versus host disease (GVHD), which has been recently associated with the appearance of a DP T cell population that was originally not present in the graft [72].…”
mentioning
confidence: 99%
“…Chicken-specific studies suggest that these cells are of a CD4 + T cell origin ( 54 ) and that their presence in the periphery increases with age (Erf et al., 1998) ( 55 ). Recent data from mammals suggest that CD4 + CD8α + are antigen-experienced and possibly of CD8-origin ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, its negative effects were found in some studies. One study found that reveals human DPTs as a T cell population directly involved with graft-versus-host disease (GVHD) pathology ( 68 ). Expansion of DPT cells is associated with joint damage and frequent escalation of therapy, possibly suggesting a contribution to more severe rheumatoid arthritis ( 69 ).…”
Section: Discussionmentioning
confidence: 99%